Biochemistry of archaea (archaebacteria) - Kates, Morris; Kushner, Donn; Matheson, A. T (New Comprehensive Biochemistry, 1993)
In the last 10 years, considerable information has accumulated on the biochemistry of archaea. In this volume, the subject as a whole is treated in a comprehensive manner. The book brings together recent knowledge concerning general metabolism, bioenergetics, molecular biology and genetics, membrane lipid and cell-wall structural chemistry and evolutionary relations, of the three major groups of archaea: the extreme halophiles, the extreme thermophiles, and the methanogens.Subjects included are: the evolutionary relationship of these microorganisms to all other living cells; special metabolic features of archeaea; protein structural chemistry; cell envelopes; molecular biology in archaea including DNA structure and replication, transcription apparatus, translation apparatus, and ribosomal structure; and a final chapter on the molecular genetics of archaea. This comprehensive scope ensures its usefulness to researchers, and stimulates further study in this rapidly developing field.